PROSEDUR PINJAMAN TANGGUNG RENTENG UNTUK MODAL USAHA UMKM PADA UNIT JASA KEUANGAN KOPERASI GARUDAYAKSA NUSANTARA (KGN) - Tannia Regina; Tedi Rochendi; Arya Nanda Pratama (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
The Joint Liability Loan Procedure for UMKM at the Unit Jasa Keuangan Koperasi Garudayaksa Nusantara. This research is a qualitative research with a descriptive design. The purpose of this study is to describe and determine the implementation of joint responsibility loans starting from the marketing process of jointly and severally loan products, the formation of jointly and severally responsibility groups, the application of jointly and severally responsible loans to UJK KGN, the process of analyzing the feasibility test of joint responsibility, to the process of disbursement of jointly and severally loans. The joint responsibility loan is used by UJK KGN customers as business capital to run their UMKM business operations. The results showed that the joint responsibility loan procedure had been carried out properly and in accordance with standard operating procedures at UJK KGN but in practice there were still UJK KGN customers whose installments were in arrears and the repayment of loan installments did not match the due date